Options and decision-making: hypertensive disorders of pregnancy. (July 2010) - Chandiramani, Manju; Joash, Karen; Shennan, Andrew H
Hypertension remains the most commonly encountered medical condition in pregnant women, complicating up to 15% of all pregnancies. It results in frequent hospital admissions, maternal morbidity and mortality and iatrogenic preterm birth with concomitant neonatal morbidity and mortality. Hypertensive disorders of pregnancy comprise a spectrum of severity ranging from a mild elevation of blood pressure to severe pre-eclampsia and hemolysis, elevated liver enzymes and low platelet syndrome that may result in transient or chronic multiorgan failure. As regular antenatal surveillance is the only manner by which to accurately identify those who are at risk, antenatal care schedules have been designed to detect hypertension and proteinuria. Early referral for specialist care for those who are at risk and those who develop hypertension is encouraged in the hope that this will translate into improved management of women with prophylactic, antihypertensive and anticonvulsant therapy. Advances in the understanding of the pathophysiology of the hypertensive disorders of pregnancy are likely to influence future research into both identifying those who are at risk and the role of interventions, and so lead to improved maternal and neonatal outcomes. This article highlights the pathophysiology of these conditions, the classification and identification of high-risk women, clinical manifestations and options for management.